A Psychospiritual Model of Emotion Regulation in Pesantren Counseling - Muhimmatul Hasanah; Anas Alhifni; Lutfiyah Khur’in (Jurnal Psikologi Teori dan Terapan, 2026)
Background: Adolescents in Islamic boarding schools (pesantren) encounter emotional challenges such as adaptation stress, academic pressure, peer conflict, and withdrawal within structured religious environments. In this context, counselors function as spiritual mentors and facilitators of emotional regulation. Objective: This study examines how psychospiritual mechanisms are constructed in pesantren counseling practices and formulates a Psychospiritual Emotion Regulation Model (PERM). Method: A qualitative case study was conducted at Pondok Pesantren Sunan Drajat involving five counselors and ten santri who had experienced emotional difficulties. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using thematic and analytic model construction procedures. Results: Findings indicate that emotional triggers activated two interconnected regulatory processes: cognitive reappraisal facilitated through structured counseling techniques and spiritually mediated meaning reconstruction grounded in practices such as taubah, sabr, and muhasabah. These processes operated reciprocally within the institutional ecology, contributing to behavioral adjustment, enhanced emotional awareness, and internalized spiritual meaning. Conclusion: The proposed PERM conceptualizes emotion regulation as a dual psychospiritual process embedded in a moral-educational context. Derived from a single-case qualitative inquiry, the model offers a contextually grounded specification of emotion regulation theory for faith-based counseling settings. Abstrak Latar Belakang: Remaja di lingkungan pesantren menghadapi berbagai tantangan emosional, seperti stres adaptasi, tekanan akademik, konflik teman sebaya, dan kecenderungan penarikan diri dalam sistem pendidikan religius yang terstruktur. Dalam konteks ini, konselor berperan sebagai pembimbing spiritual sekaligus fasilitator regulasi emosi. Tujuan: Penelitian ini menganalisis konstruksi mekanisme psikospiritual dalam praktik konseling pesantren dan merumuskan Psychospiritual Emotion Regulation Model (PERM). Metode: Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus di Pondok Pesantren Sunan Drajat, melibatkan lima konselor dan sepuluh santri yang mengalami kesulitan emosional. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen, kemudian dianalisis secara tematik melalui konstruksi model analitik. Hasil: Temuan menunjukkan bahwa pemicu emosional mengaktifkan dua proses regulasi yang saling berinteraksi, yaitu restrukturisasi kognitif melalui teknik konseling terstruktur dan rekonstruksi makna berbasis spiritual melalui praktik taubah, sabr, dan muhasabah. Interaksi keduanya berlangsung dalam ekologi institusional pesantren dan berkontribusi pada penyesuaian perilaku, peningkatan kesadaran emosi, serta internalisasi makna spiritual. Kesimpulan: PERM memosisikan regulasi emosi sebagai proses psikospiritual ganda yang terintegrasi dalam konteks moral-edukatif. Model ini bersifat kontekstual dan menawarkan spesifikasi teoritis regulasi emosi dalam layanan konseling berbasis religiusitas.